FEATURES OF USING VBA IN TEACHING ACTUARIAL MATHEMATICS - Zubchenko, Volodymyr; Yamnenko, Rostyslav (Physical and Mathematical Education, 2024)
The article is devoted to the analysis of practice of application of specific computational techniques within MS Excel, including VBA, for teaching selected topics in actuarial mathematics. Formulation of the problem. With the evolution of financial and actuarial models towards complexity and reliance on machine learning and data science, there is a growing demand for modern mathematicians, particularly actuaries, to acquire new skills and knowledge. This demand is being driven by new fintech trends in banking and insurance, such as smart payments, real-time credit risk assessment, automated reputation management, customer analytics, fraud detection and cryptocurrency trading. As a result, the training of future actuaries must meet high standards to ensure they are equipped to handle the sophisticated mathematical calculations required by insurance companies and other financial institutions. Materials and methods. To yield results, both theoretical methods, which involve analyzing books and publications, in particular in professional journals in the domains of finance and actuarial mathematics, and empirical methods, entailing the observation of the educational process aimed at training prospective actuaries, are employed in this study. Results. A study aimed at tackling the challenges encountered in teaching actuarial mathematics topics, such as life expectancy and mortality tables, revealed that incorporating a balanced blend of theoretical concepts and hands-on applications, coupled with illustrating mathematical models through real-world examples and reinforcing diverse computational techniques, constitutes a cornerstone of successful training for aspiring actuaries. Leveraging a versatile and user-friendly tool like VBA (Visual Basic for Applications) integrated into MS Excel enables educators to customize examples and assignments to match the intricacy and emphasis of their syllabus, thereby offering students a more targeted learning journey. Conclusions. The teaching of mathematical disciplines, especially financial and actuarial mathematics, in academic programmes for future actuaries requires the adaptation of traditional methods and approaches. In particular, the integration of VBA is key to teaching specific actuarial mathematics concepts, which aims to equip students with the necessary practical competencies. VBA facilitates interactive learning by enabling students to manipulate variables and observe changes in calculations in real time, which improves their understanding of actuarial concepts. VBA also allows you to automate repetitive tasks involving complex mathematical calculations, which saves time and reduces errors. Therefore, its use is recommended when teaching topics involving tabular data, especially life expectancy.